The Freeze-Drying of Pharmaceuticals in Vials Nested in a Rack System-Part II: Primary Drying Behaviour - Fiora Artusio; Marco Adami; Antonello A. Barresi; Davide Fissore; Maria Chiara Frare; Claudia I. Udrescu; Roberto Pisano (MDPI AG, 2023)
The freeze-drying of biopharmaceuticals is a common strategy to extend their shelf-life and facilitate the distribution of therapeutics. The drying phase is the most demanding one in terms of energy consumption and determines the overall process time. Our previous work showed how the loading configuration can impact freezing. This paper focuses on primary drying by comparing the thermal behaviour of vials loaded in direct contact with the shelf or nested in a rack system. The overall heat transfer coefficient from the apparatus to the product was evaluated at different chamber pressures (5-30 Pa) and shelf temperatures (from −10 °C to +30 °C), and in the case of various vial positions (central, semi-border, and border vials). Because of the suspended configuration, the heat transfer coefficient was less affected by chamber pressure in vials nested in a rack system. The two loading configurations displayed comparable heat transfer efficiency below 10 Pa. For higher chamber pressure, the heat transfer coefficients of nested vials were lower than those of vials in direct contact with the shelf. Nevertheless, the rack system was beneficial for reducing the inter-vial variability as it promoted higher uniformity in the heat transfer coefficients of central vials. Eventually, thermal image analyses highlighted limited temperature differences between the vials and the rack system.